The Impact of School Classroom Chair Depth and Height on Learning Tasks - Hsiu-Feng Chen; Chih-Yung Tsai (Education Sciences, 2024)
The purpose of this study is to investigate the effect of the seating condition on learning tasks. This physical setting and these cognitive activities (that participants then test) are not the totality of education practice and context, but desks and chairs are important physical elements for students to learn, because students always spend so much time learning at their seats. At present, the chairs purchased by the school have uniform specifications, so they cannot be customized. To provide students with more comfort, their sitting condition and backrest are commonly adjusted. This study investigated the effects of the sitting condition on the performance of short learning tasks that require high concentration, namely short-term number memorization, mathematical calculations, and logical judgment, through a two-way within-subjects design (seat depth and backrest height). Thirty adults over 20 years old, with visual acuity (including corrected visual acuity) greater than 0.7 and no history of musculoskeletal disease, participated in this experiment. The results indicated that seat depth and backrest height had an interaction effect on task performance. Sitting on the front third of a chair with a lower backrest produced excellent learning tasks outcomes; seat configuration may affect student performance on learning tasks. Thus, schools and educational institutions can try to require students to temporarily sit in this sitting condition to perform such tasks. In addition, schools can purchase chairs with a lower backrest and require that students use lumbar pads to adjust the seat depth to achieve superior learning task outcomes in classrooms.